PENDAMPINGAN PEMANFAATAN APLIKASI BUKU WARUNG PADA UMKM KRUPUK BERKAH PIALA DI DESA DLIMAS - Assaniyatun Khasinah; Ahmad Muhibin (khidmatan, 2024)
The UMKM (Micro, Small, and Medium Enterprise) Krupuk Berkah Piala, established in 2002 on the initiative of Ibu Isfaiyyah and managed by the Dlimas Village community, is a micro enterprise with significant potential. The objective of this community service program was to analyze and improve the financial management system of the UMKM. The methodology employed was the Asset Based Community Development (ABCD) approach, with data collection through observation and interviews. Observations revealed a serious constraint: the financial reporting system was still manual, leading to undisciplined recording, calculation errors, and suboptimal financial management. To overcome these deficiencies, the engagement team provided a solution by transitioning the manual financial system to a digital one through intensive assistance in utilizing the Buku Warung Application. This intervention successfully transformed the bookkeeping process, providing ease in financial management and reporting, thereby supporting UMKM Krupuk Berkah Piala in achieving better accountability and efficiency.